History of Islamic Banking Performance Comparison to Western Banking - Kolštrom, Jan; Szobi, Pavel, 1983-; Johnson, Zdenka, 1983-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2013)
This diploma thesis is focused on comparison between conventional (interest based)and Islamic (profit-loss sharing based) banking systems. I examine historical and institutional development of the Islamic banking sector, from its very beginning up till today. I am paying great attention to development of the institutions related to stability of banking system, mostly regulative ones and I focus on the impact of these regulations on the Islamic banking system in period of subprime mortgage crisis. Main questions of the thesis are; how differences between both banking systems influence their performance during financial crisis and what factors are the most important ones in this divergence. Main hypotheses stand as follow: Performed Islamic banking sector better during period of the financial crisis and if, then why? I verify this hypothesis both theoretically and empirically. I study above mention problem from postmodern critical point of view based on economic history methodology.
Vedoucí práce: Pavel Szobi
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: hospodářské a politické dějiny 20. století [obor dipl. práce]; diplomové práce; master's theses